Situating The Notion of Nationalism in Whitman’s “Song of Myself” and Roy’s The God of Small Thing - Dian Windriani (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
The idea of nationalism cannot be universalized, proven by Hans Kohn’s framework on Civic and Ethnic nationalism. Applying Hans Kohn’s framework on nationalism, this study examines the act of nationalism reflected in Walt Whitman’s “Song of Myself” (1855) and Arundhati Roy’s The God of Small Things (1997). This study uses qualitative research method by employing three steps in interpreting the data; describing, analysing, and deriving a conclusion. This study finds out that first, Whitman’s “Song of Myself” (1855) glorifies individual journey and struggle in uniting the whole members of the nation. Second, Roy’s The God of Small Things (1997) highlights the collective cultural identity as a form of rejection to colonial supremacy. Due to the controversy of Hans Kohn’s framework on nationalism, the contextualization of the writer’s background and social history of the works is needed.